281 Metastatic Collision Tumors: A Clinicopathologic Review. (11th January 2018) - Mahmud, Waqas; Rohra, Prih; Bitterman, Pincas; Reddy, Vijaya; Gattuso, Paolo
Abstract: Objectives: Metastatic collision tumors, although a well-known clinicopathological entity is only rarely encountered in clinical practice. We reviewed the clinicopathologic features in a series of metastatic collision tumors. Methods: The surgical pathology files from 1994 to February 2017 at our institution were searched for metastatic collision tumors. Results: A total 15 cases of metastatic collision tumors were identified. Six patients were men, and nine women. The mean age was 71.6 years. Special studies were performed in in 12 out of 15 cases to confirm metastasis. Conclusion: Metastatic collision tumors are uncommon lesions. Ancillary studies are helpful in supporting the routine microscopic findings. Hematological malignancies were the most common primary tumor (60%) followed by meningioma (27%). Breast carcinoma was the most common metastatic tumor (27%). Metastatic collision tumors have to be recognized as they may dictate a change in management strategy.